2010
DOI: 10.1111/j.1365-2966.2010.16290.x
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing in a non-uniform plasma

Abstract: We develop a model of gravitational lensing in a non-uniform plasma. When a gravitating body is surrounded by a plasma, the lensing angle depends on the frequency of the electromagnetic wave, due to dispersion properties of plasma, in presence of a plasma inhomogeneity, and of a gravity. The second effect leads, even in a uniform plasma, to a difference of the gravitational photon deflection angle from the vacuum case, and to its dependence on the photon frequency. We take into account both effects, and derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
175
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(185 citation statements)
references
References 20 publications
10
175
0
Order By: Relevance
“…In [27,28] we have found that in the absence of refraction, in a uniform dispersive medium, when the refractive index depends on the photon frequency, the gravitational deflection is qualitatively different from the vacuum case, and the deflection angle depends on the photon frequency (see Fig. 3).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In [27,28] we have found that in the absence of refraction, in a uniform dispersive medium, when the refractive index depends on the photon frequency, the gravitational deflection is qualitatively different from the vacuum case, and the deflection angle depends on the photon frequency (see Fig. 3).…”
Section: Introductionmentioning
confidence: 94%
“…Applying the general theory to plasma, that is a dispersive medium, and its refractive index depends on the photon frequency, we have obtained a simple analytical formula for the light deflection in a Schwarzschild metric, in presence of a homogeneous plasma [27]. In [28] we developed a more general approach, considering an inhomogeneous plasma, where a nongravitating refractive deflection was also taken into account. All the results have been obtained in the approximation of a small deflection angle.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Now using the Hamilton-Jacobi equation which defines the equation of motion of the photons for a given space-time geometry [4,22,24]:…”
Section: Photon Motion Around the Black Hole In The Presence Of Pmentioning
confidence: 99%
“…For example, the gravitational lensing in inhomogeneous and homogeneous plasma around black holes has been recently studied in [4][5][6][7][8] as extension of vacuum studies (see, e.g. [9,10]).…”
Section: Introductionmentioning
confidence: 99%